2008
DOI: 10.1016/j.clim.2007.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Increased circulating interleukin (IL)-23 in children with malarial anemia: In vivo and in vitro relationship with co-regulatory cytokines IL-12 and IL-10

Abstract: Severe malarial anemia (SMA) is a leading cause of mortality among children in sub-Saharan Africa. Although the novel cytokine, interleukin (IL)-23, promotes anemia in chronic inflammatory diseases, the role of IL-23 in SMA remains undefined. Since IL-23 and IL-12 share the IL-12p40 subunit and IL-12Rβ1 receptor, and are down-regulated by IL-10, relationships among these cytokines were explored in Kenyan children with varying severities of malarial anemia. Children with malarial anemia had increased circulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
38
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 52 publications
4
38
1
Order By: Relevance
“…This mode of protection is quite novel in the IL-23/IL-17 axis of inflammation. As human malaria parasites also induce IL-23 [45], our findings provide insight into the immune mechanisms that are important to take into account malaria vaccine development or therapeutic strategies based upon IL-23.…”
Section: Discussionmentioning
confidence: 99%
“…This mode of protection is quite novel in the IL-23/IL-17 axis of inflammation. As human malaria parasites also induce IL-23 [45], our findings provide insight into the immune mechanisms that are important to take into account malaria vaccine development or therapeutic strategies based upon IL-23.…”
Section: Discussionmentioning
confidence: 99%
“…11 There is a growing body of evidence for a key role of IL-12 in the immune response directed against Plasmodium species, whereas IL-23 was only recently proposed to be involved in malaria. 12 Neutralization of endogenous IL-12 with anti-IL-12p40 and anti-IL-12p35 antibodies in P. chabaudiinfected mice resulted in an increase of parasitemia, 13 whereas administration of recombinant IL-12 in mice and monkeys conferred a protection from Plasmodium species infection. 13,14 Studies with IL-12p40-deficient mice confirmed the effect of IL-12 in the protection against P. chabaudi.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-inflammatory cytokines also play an important role in malarial pathogenesis through their ability to modulate the proinflammatory response. For example, IL-10 levels increase progressively with enhancing severity of childhood malarial anemia and parasite density (38) and are associated with an inability to clear malaria parasitemia (15). Increased circulating levels of IL-1 receptor antagonist (IL-1Ra) are also associated with enhanced malaria disease severity in African children (17,20), while reduced production of other anti-in-flammatory cytokines, such as transforming growth factor beta (TGF-␤), correlate with severe malaria (41).…”
mentioning
confidence: 99%
“…Elevated levels of proinflammatory cytokines, including interleukin 1␤ (IL-1␤), IL-6, IL-8, IL-23, gamma interferon (IFN-␥), and tumor necrosis factor alpha (TNF-␣), are associated with enhanced disease severity in human malaria (17,22,27,38). Conversely, decreased levels of additional proinflammatory cytokines, such as IL-12 and IFN-␣, are associated with enhanced malaria pathogenesis in humans (22,26,38,41). Anti-inflammatory cytokines also play an important role in malarial pathogenesis through their ability to modulate the proinflammatory response.…”
mentioning
confidence: 99%